(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Since the advent of high-throughput sequencing technologies, organised germline screening, independent of the personal and family cancer history, has been frequently proposed. Since ethnic and geographic populations significantly differ in their mutation spectra and prevalence, one critical prerequisite would be the knowledge of the expected carrier frequencies. OBJECTIVE For the first time, in a retrospective non-cancer related cohort from a single Swiss genetic centre, we systematically assessed the prevalence of secondary findings in 19 genes (BRCA1/2 plus 17 non-BRCA genes) previously designated by the US National Comprehensive Cancer Network (NCCN) for hereditary breast and ovarian cancer (HBOC) germline testing. DESIGN A total of 400 individuals without a cancer diagnosis undergoing whole-exome sequencing (WES) analysis for neurodevelopmental disorders (NDDs) from 2015 to 2017 at IMG Zurich were included after quality assessment. Among these, 180 were unaffected parental couples, 27 unaffected parental singles and 13 NDD index patients (mean age 43 years). The majority of the cohort was of Caucasian ethnicity (n = 336, 84.0%) and of Northwest European ancestry (n = 202, 50.5%), for 70 of whom (42.5%) an autochthonous Swiss descent was assumed. For WES filtering of rare, potentially actionable secondary variants in HBOC genes, an overall minor allele frequency (MAF) below 0.65% was used as cut-off. Each rare variant was manually evaluated according to the recommended ACGM-AMP standards, with some adaptations including “hypomorphic” as an additional distinct pathogenicity class. RESULTS Overall, 526 rare secondary variants (339 different variants) were encountered, with the BRCA1/2 genes accounting for 27.2% of the total variant yield. If stratified for variant pathogenicity, for BRCA1/2, three pathogenic variants were found in three females of Italian ancestry (carrier frequency of 0.8%). In the non-BRCA genes, five carriers of (likely) pathogenic variants (1.3%) were identified, with two Swiss individuals harbouring the same CHEK2 Arg160Gly variant known to be recurrent among Caucasians. Hence, the overall carrier rate added up to 2.0%. Additionally, seven various hypomorphic HBOC predisposing alleles were detected in 22 individuals (5.5%). CONCLUSION We provide the first evidence of a high prevalence of HBOC-related cancer susceptibility in the heterogeneous Swiss general population and relevant subpopulations, particularly in individuals of Italian descent. These pioneering data may substantiate population-based HBOC screening in Switzerland.